Influence Of Brand Image, Service Quality, Customer Experience, And Trust Through Customer Satisfaction As Intervening Variable On Customer Loyalty At Celebrity Fitness Member In Jabodetabek Area - Felicia Vania Dwinata Tamin; Margaretha Pink Berlianto (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The purpose of this research is to determine the effect of moderating variables on the relationship between Brand image, Service Quality, Customer Experience, and Trust on Customer Satisfaction as intervening variables to build Customer Loyalty among Celebrity Fitness members in the JABODETABEK area. Data was obtained by distributing questionnaires with a Descriptive Quantitative approach. There were 194 Respondents obtained from this research. The sampling technique used was non-probability sampling. Data were analyzed using Structural Equation Model with Analysis tools Smart-PLS. The results of this study indicate that Based on the analysis produced by PLS-SEM, it can be found that 7 out of 8 research hypotheses can be accepted. Based on this analysis, it can be concluded that in order to build customer loyalty, Celebrity Fitness must pay attention to several important factors in this research variable. Various variables that can increase the loyalty of a customer that has the strongest effect is to increase customer satisfaction.